Prevalence and outcome of HIV infected children admitted in a tertiary hospital in Northern Tanzania - Tulla S. Masoza; Raphael Rwezaula; Delfina R. Msanga; Neema Chami; Julieth Kabirigi; Emmanuela Ambrose; Restituta Muro; Stella Mongella; Adolfine Hokororo; Elizabeth Kwiyolecha; Robert Peck (BMC, 2022)
Abstract Background Provider Initiated Testing and Counseling (PITC) among hospitalized children have shown to increase the probability of identifying HIV-infected children and hence be able to link them to HIV care. We aimed at determining the prevalence, clinical characteristics and outcome of HIV-infected children admitted at Bugando Medical Centre (BMC) after active provision of PITC services. Methods A cross-sectional study with follow up at three months post enrollment was done. Children with unknown HIV status were tested for HIV infection as per 2012 Tanzanian algorithm. Questionnaires were used to collect demographic, clinical and follow up information. Data was statistically analyzed in STATA v13. Results A total of 525 children were enrolled in the study. Median [IQR] age was 28 [15-54] months. Males consisted of 60.2% of all the participants. HIV prevalence was 9.3% (49/525). Thirty-three (67.3%) of HIV-infected children were newly diagnosed at enrolment. Thirty-nine (79.6%) of all HIV-infected patients had WHO HIV/AIDS clinical stage four disease, 10 (20.4%) had WHO clinical stage three and none qualified in stage one or two. About 84% (41/49) of HIV infected children had severe immunodeficiency at the time of the study. Factors that were independently associated with HIV infection were, cough (OR 2.40 [1.08-5.31], p = 0.031), oral thrush (OR 20.06[8.29-48.52], p < 0.001), generalized lymphadenopathy (OR 5.61 [1.06-29.56], p = 0.042), severe acute malnutrition (OR 6.78 [2.28-20.12], p = 0.001), severe stunting (OR 9.09[2.80-29.53], p = 0.034) and death of one or both parents (OR 3.62 [1.10-11.87], p = 0.034). The overall mortality (in-hospital and post-hospital) was 38.8% among HIV-infected children compared with 14.0% in HIV-uninfected children. Within three months period after discharge from the hospital, 71.4% (25/35) of discharged HIV-infected children reported to have attended HIV clinic at least once and 60.0% (21/35) were on antiretroviral medications. Conclusion PITC to all admitted children identified significant number of HIV-infected children. Mortality among HIV-infected children is high compared to HIV-uninfected. At the time of follow up about 30% of discharged HIV-infected children did not attend to any HIV care and treatment clinics. Therefore effective efforts are needed to guarantee early diagnosis and linkage to HIV care so as to reduce morbidity and mortality among these children.